Food Neophobia in Children with Autistic Spectrum Disorder (ASD): A Nationwide Study in Brazil - Priscila Claudino de Almeida; Renata Puppin Zandonadi; Eduardo Yoshio Nakano; Ivana Aragão Lira Vasconcelos; Raquel Braz Assunção Botelho (MDPI AG, 2022)
Food neophobia (FN) is common among children with autistic spectrum disorder (ASD), potentially impairing their health and diet quality. This study aimed to investigate and classify the prevalence of FN among 4-to-11-year-old Brazilian children with ASD. This descriptive cross-sectional study was performed by applying online a validated instrument to identify FN in Brazilian children with ASD through their caregivers' responses for a national prevalence of FN in this group. The final sample included 593 children with ASD, 80.1% of boys, with a mean age of 6.72 ± 2.31 years, and 83% having only ASD. Almost 75% (n = 436) of the children with ASD had high food neophobia scores. The fruit neophobia domain had the lowest prevalence of high neophobia (63.7%). No significant difference in FN (total, fruit, and vegetable domains) was found, considering gender and age. There was no statistical difference in FN (all domains) by the number of residents in the same household, income, or the caregivers' educational level. FN did not decrease in older children with ASD. FN is a more complex problem, requiring a multidisciplinary trained team to face the problem.